The Nutritive Potentials of Sweet Orange (Citrus sinensis) Rind in Broiler Production - Oluremi, O.I.A.; Ojighen, V.O.; Ejembi, E.H. (International Journal of Poultry Science, 2006)
A feeding trial was conducted with one week old one hundred and fifty Anak broiler chickens to assess the nutritive potentials of sun dried sweet orange (Citrus sinensis) rind (SOR). They were randomly assigned to five dietary groups in which rind replaced maize at 0, 5, 10, 15, and 20% levels in both starter and finisher diets. Each group had thirty broilers and replicated thrice. The birds were fed ad libitum for a nine-week period during which performance indices and carcass cuts and organs were evaluated. Experimental diets had no significant effect (p>0.05) on feed intake, body weight gain, water consumption, water: feed ratio, feed conversion ratio and feed cost per broiler while final live weight was affected significantly (p< 0.05). Increasing dietary SOR content beyond 15% reduced growth rate, which cumulatively caused a decrease in final live weight. Diets had significant effect only thigh+drumstick and the abdominal fat, and the dressing percentage values of broilers on the SOR diets were higher those on the control. The liver of chickens on the 20% SOR replacement treatment manifested hypoplasia. The study has shown that dried SOR can be used to replace dietary maize in the diet of broilers at 15% level.